03 Temperature post out-of-hospital cardiac arrest: the TOPCAT study. Issue 3 (1st March 2011) - Lyon, Richard; Richardson, Sarah; Gowens, Paul; Egan, Gerry; Hay, Alasdair; Andrews, Peter; Clegg, Gareth
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) remains the leading cause of sudden death faced by EMS personnel. Therapeutic hypothermia has been shown to improve neurological outcome and survival in certain patients after out-of-hospital cardiac arrest. The natural progression of core body temperature, particularly in the pre-hospital setting, post OHCA has yet to be established. Pre-hospital core body temperature will influence the need for possible pre-hospital cooling post OHCA. Aims: To establish the natural progression of core body temperature after OHCA. Methods: One year, prospective observational study across the Lothians region of Scotland. A research doctor was tasked by the Emergency Medical Dispatch Centre to attend patients in OHCA together with the attending ambulance crew. An oesophageal core body temperature probe was inserted to continuously monitor core body temperature from the earliest opportunity in the field to arrival of the patient on the Intensive Care Unit (ICU). Therapeutic hypothermia was commenced after admission to the ICU. Results: 147 OHCA were included. 13 patients survived to reach hospital discharge (8.8%). After return of spontaneous circulation (ROSC) core body temperature increased until therapeutic cooling commenced. Re-warming occurred faster in survivors. There was no significant pre-hospital core body temperature difference between survivors (33.03°C) and non-survivors (33.58°C). Patients surviving to discharge had a higher core body temperature on arrival in ITU compared to non-survivors (35.44°C vs 34.25°C, p<0.05). Conclusions: OHCA patients in our area remain cool (<35C) during the pre-hospital phase. This may suggest that pre-hospital cooling is not required for these patients. This is the first study of its kind to report on core body temperature after OHCA. Survivors rewarming faster has not yet been described and the mechanisms underlying this required further investigation. Further research is warranted into the mechanisms of action of therapeutic hypothermia, particularly the optimum timing and method of cooling.